European Economic sanctions against Russia and effects - K. A. Azhekbarov; E. Ch. Abduvaitov (Путеводитель предпринимателя, 2020)
The article outlines the essence of the economic sanctions imposed on Russia by the Western EU countries, as well as other countries of the Allies. This article gives the reasons for the sanctions, how they have affected the macro and micro economy and what to expect in the future. The main purpose of the article was to identify the risks and consequences of EU economic sanctions against Russia, as well as how they will affect the CIS countries. The article presents analysis of the consequences of economic sanctions on the entire development sector of Russia, on import and export markets, on the sector of finance, investment, tourism.